MAIRIL : PHENOMENA HOMOSEKSUALITAS DI PESANTREN - , Usman, Prof. Drs. H. Koentjoro, MBSc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research an aimed to understand psychological intrumens develop to analyze 9 participants was dynamic of ngepe practices. Phenomenological with in more depth interview from Participants are four santri, five informan. This research used in-depth interviews to collect data from four participants and five informants. Phenomenological method of analysis used to interpretative the data it included bracketing, horizonalizing, meaning units to get the description of textural, imaginative variation to get structural description, and blend (composite) description of textural and structural became one of universal significance that represent participants overall. Research results show that the participants at the beginning of time in boarding school had refused even to hate oriented as mairil, but in turn they receive be mairil, because they feel happy and get sexual satisfaction